The Social and Emotional Well-being of Indigenous Peoples Living With Diabetes: A Systematic Review Protocol - Speight, Jane; Baptista, Shaira; Lee, Christopher; Sher, Louisa; Skinner, Timothy C.; Brown, Alex (Frontiers in Clinical Diabetes and Healthcare, 2022)
Introduction Globally, Indigenous people have a greater incidence and earlier onset of diabetes than the general population and have higher documented rates of emotional distress and mental illness. This systematic review will provide a synthesis and critical appraisal of the evidence focused on the social and emotional well-being of Indigenous peoples living with diabetes, including prevalence, impact, moderators, and the efficacy of interventions. Methods We will search MEDLINE Complete, EMBASE, APA PsycINFO, and CINAHL Complete from inception until late April 2021. Search strategies will include keywords related to Indigenous peoples, diabetes, and social and emotional well-being. All abstracts will be rated independently by two researchers against specified inclusion criteria. Eligible studies will report social and emotional well-being data for Indigenous people with diabetes, and/or report on the efficacy of interventions designed to address social and emotional well-being in this population. For each eligible study, quality will be rated using standard checklists to appraise each study’s internal validity, to be determined based on study type. Any discrepancies will be resolved through discussions and consultation with other investigators as needed. We expect to present a narrative synthesis of the evidence. Discussion The findings of the systematic review will enable greater understanding of the impact of relationships between diabetes and emotional well-being among Indigenous peoples to inform research, policy and practice. The findings will be accessible to Indigenous people affected by diabetes through a summary published in plain language on our research centre’s website. PROSPERO registration number: CRD42021246560.